Development of an Innovative Magnetorheological Gearbox for Positioning Control and Anti-Disturbance of a Robotic Arm - Yuyang Zhang; Shuaishuai Sun; Lei Deng; Guorui Wang; Rui Yu; Weihua Li; Xinglong Gong; Shiwu Zhang; Haiping Du; Jian Yang (Machines)
The robotic arm is a critical component of modern industrial manufacturing. However, its positioning performance can be hindered by overshooting and oscillation. External disturbances, including collisions or impacts with other objects, can also affect its accuracy and precision. To resolve this problem, this work integrates a compact magnetorheological (MR) bearing, which is capable of switching between locking and unlocking states utilizing the MR effect, into the gearbox of the actuation system of the robotic arm. This integration enables the gearbox (referred to as the MR gearbox) to exhibit variable damping characteristics. This controllable damping property will play an important role in improving the positioning accuracy by offering additional damping. In this study, the MR gearbox was first designed and prototyped. A characterization test was then conducted to verify its variable damping property. The classic Bouc–Wen model was used to describe the MR gearbox and then a mathematical model was established for the whole robotic arm. Additionally, a new variable damping control method was proposed for further improving the positioning precision and reducing energy consumption. As follows, the positioning and the anti-disturbance performances of the robotic arm system installed with the MR gearbox were assessed through numerical simulations and experimental tests. The result shows that the robotic arm under the new control method achieves reductions of 11.76% in overshoot, 14.73% in settling time, and 26.1% in energy consumption compared to the uncontrolled case under the step trajectory, indicating improved positioning performance.